Oncological approach with antihelminthic chemotherapy and wide resection in the treatment of musculoskeletal hydatidosis. A review of 10 cases with mean follow-up of 64 months - (:unkn) unknown (ACTA MEDICA BELGICA, 2015)
The objective of this retrospective study was to evaluate clinical outcomes, local recurrence and complication rates of antihelminthic chemotherapy and wide resection in patients with muscle or bone hydatidosis. The authors treated 10 patients (6 females, 4 males) between 2004 and 2012: 8 with muscle and 2 with bone hydatidosis. The mean age at surgery was 42.5 years (range, 11-66 years). All patients were treated with wide resection and pre- and postoperative chemotherapy with albendazole. The mean follow-up was 64 months (range, 28-120 months). All patients achieved satisfactory clinical outcomes. There were no local recurrences. Surgical complications were seen in 3 patients (30%) : one superficial infection, one deep infection, and one hematoma. Two (20%) required additional surgery. An aggressive oncological approach, consisting of antihelminthic chemotherapy and wide resection, can provide favorable clinical outcomes and prevent local recurrence in patients with musculoskeletal hydatidosis. Potential complications of aggressive surgery should be preferred to potential morbidity of local and systemic dissemination.
Keywords: hydatidosis; muscle; bone; antihelminthic chemotherapy; wide resection; PRIMARY INTRAMUSCULAR HYDATIDOSIS; ECHINOCOCCUS INFESTATION; OSSEOUS HYDATIDOSIS; BONE HYDATIDOSIS; DISEASE; CYST; MUSCLE